Heavy Metal Content in Green Mussels (Perna viridis) Cultivated in Ketapang Village, Tangerang Regency: Kandungan Logam Berat pada Kerang Hijau (Perna viridis) yang Dibudidayakan di Desa Ketapang, Kabupaten Tangerang - Dwi Ernaningsih; Patanda, Mercy; Rahmani, Urip; Telussa, Riena F. (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2023)
The aims of the study were: (1) to test the metal content in green mussels; (2) testing the metal content in seawater for aquaculture activties; and (3) calculating green mussel business income. The research was conducted in May-July 2022 at four locations, three locations in the green mussel cultivation area and the fourth location in the green mussel collection area owned by a fisherman. Selection of sampling locations by purposive sampling. Primary data was collected by field survey methods and interviews with 9 green mussel cultivators. Secondary data was obtained from the Department of Maritime Affairs and Fisheries of the Tangerang Regency and scientific publications, including other research supporting data. Data analysis of metal content in green mussels according to the Indonesian National Standard (SNI) No. 7387-2009; Analysis of heavy metal content in seawater refers to the government regulation No 22 of 2021 concerning on the implementation of environmental protection and management seawater quality standards, especially for marine life; identification of trap catches was analyzed descriptively; analysis of green mussels chart business income using net income (????), R/C ratio, and payback period. The results showed that the metal content in green mussels at location 1 exceeded the threshold value compared to the other three locations; all metal content in sea water does not exceed the threshold value. This means that the mussels can still be consumed by the public and the waters are good for mussel cultivation. Mud grouper is the main catch of traps associated with green mussel cultivation sites and the highest R/C in respondents No. 1 and 6 with a payback period of <3 years, showing that the rate of return on business capital is categorized as fast.